34.0k views
4 votes
Which procedure justifies whether Negative 3 x (5 minus 4) + 3 (x minus 6) is equivalent to Negative 12 x minus 6? The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (2) minus 6 = negative 30. The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (3) minus 6 = negative 42. The expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (negative 2) minus 6 = 18. The expressions are equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (1) minus 6 = negative 18.

2 Answers

2 votes

Answer:

its A

Explanation:

just did the quiz on edge 2020

User Anthony McGovern
by
4.3k points
3 votes

Answer:

The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (2) minus 6 = negative 30

Explanation:

Apparently, we're trying to see if ...

-3(x)(5 -4) + 3(x -6) = -12(x) -6

by evaluating the expressions for x=2:

-3(2)(5-4) +3(2 -6) ?= -12(2) -6

-6 -12 ?= -24 -6

-18 ≠ -30 . . . . . . . . . shows expressions are not equivalent

__

This demonstration matches the one in the first choice:

The expressions are not equivalent because Negative 3 (2) (5 minus 4) + 3 (2 minus 6) = negative 18 and Negative 12 (2) minus 6 = negative 30